Single-stranded DNA oligonucleotides containing CpG motifs are non-stimulatory in vitro but offer protection in vivo against Burkholderia pseudomallei - Scott, Andrew; Farrar, Benjamin; Young, Tom; Prior, Joann; Stratilo, Chad; Unterholzner, Leonie; D’Elia, Riccardo (Frontiers in Cellular and Infection Microbiology, 2024)
Therapies that modulate and appropriately direct the immune response are promising candidates for the treatment of infectious diseases. One such candidate therapeutic is DZ13, a short, synthetic, single-stranded DNA molecule. This molecule has enzymatic activity and can modulate the immune response by binding to and degrading the mRNA encoding a key immuno-regulatory molecule. Originally developed and entering clinical trials as an anti-cancer agent, DZ13 has also been evaluated as a treatment for viral infections, and has been shown to provide protection against infection with influenza virus in a mouse model of infection. In this work, we evaluated whether the immuno-modulatory properties of DZ13 could provide protection against the potential biothreat pathogen Burkholderia pseudomallei which causes the neglected tropical disease melioidosis. Treatment of mice infected with B. pseudomallei demonstrated that DZ13 did indeed provide excellent protection after only two post-exposure treatments. However, our data indicated that the enzymatic activity contained in DZ13 was not required for protection, with control oligonucleotide treatments lacking activity against the target mRNA equally as protective against B. pseudomallei. We have designed new sequences to study the mechanism of protection further. These novel sequences offer enhanced protection against infection, but are not directly anti-microbial and do not appear to be stimulating the immune system via TLR9 or other key innate immune sensors, despite containing CpG motifs. The molecular mechanism of these novel sequences remains to be elucidated, but the data highlights that these oligonucleotide-sensing pathways are attractive and relevant targets to modulate during bacterial and viral infections.